Cyclic heat-generation and storage capabilities of self-heating cementitious composite with an addition of phase change material. (10th March 2023) - Jang, Daeik; Yoon, H.N.; Yang, Beomjoo; Khalid, Hammad R.
Highlights: Carbon nanotube- and carbon fiber-based self-heating cementitious composites. Effect of phase-change material (PCM) on their cyclic heat-generation and storage capacity. Latent heat energy increased with increase of PCM content. PCM increased the heat storage capacity by reducing the cooling speed. Abstract: This study explored the efficiency of the phase-change materials (PCM) to improve the heat storage capacity of carbon nanotube (CNT) and carbon fiber (CF) based self-heating cementitious composites. Composites were prepared with 0.8 wt% CNT and 0.2 wt% CF as conductive fillers, and five different PCM contents (0, 5, 10, 20, and 30 wt%), and their electrical conductivities, thermal conductivities, and compressive strengths were measured. To determine the self-heating capability, the heat-generation and heat-storage capabilities of the composites were investigated using monotonic and cyclic heating/cooling tests. The results of these tests were analyzed through a differential scanning calorimetry and micro-computed tomography, which showed that the PCM particles with high latent heat were well dispersed in the composites, improving the heat storage capacity. Therefore, it can be said that the addition of PCM may improve heat storage capacity and enhance energy efficiency of the cement-based self-heating composites.